Percutaneous radiofrequency ablation of solitary hepatic metastases from colorectal cancer: risk factors of local tumor progression-free survival and overall survival - Lee, Hyun Jae; Lee, Min Woo; Ahn, Soo Hyun; Cha, Dong Ik; Ko, Seong Eun; Kang, Tae Wook; Song, Kyoung Doo; Rhim, Hyunchul (Ultrasonography, 2022)
Purpose: This study aimed to evaluate local tumor progression-free survival (LTPFS) and overall survival (OS) after percutaneous radiofrequency ablation (RFA) for solitary colorectal liver metastases (CLM) <3 cm and to identify the risk factors associated with poor LTPFS and OS after percutaneous RFA. Methods: This study screened 219 patients who underwent percutaneous RFA for CLM between January 2013 and November 2020. Of these, 92 patients with a single CLM <3 cm were included. LTPFS and OS were calculated using the Kaplan-Meier method, and the differences between curves were compared using the log-rank test. Risk factors for LTPFS and OS were assessed using Cox proportional-hazard regression models. Results: Technical efficacy was achieved in the first (n=91) or second (n=1) RFA sessions. During the follow-up (median, 20.0 months), cumulative LTPFS rates at 1, 3, and 5 years were 92.4%, 83.4%, and 76.5%, respectively. During the follow-up (median, 27.8 months), the corresponding OS rates were 97.5%, 81.3%, and 74.8%, respectively. In multivariable Cox regression analyses, the group with both tumor-puncturing RFA and a T4 stage primary tumor (hazard ratio, 3.3; 95% confidence interval, 1.1 to 10.2; P=0.037) had poor LTPFS. In the univariable analysis, no factors were significantly associated with poor OS. Conclusion: Both LTPFS and OS were promising after percutaneous RFA for a single CLM <3 cm. The group with both tumor-puncturing RFA and a T4 stage primary tumor showed poor LTPFS. No risk factors were identified for poor OS.
Keywords: Colorectal neoplasms; Liver; Metastasis; Radiofrequency ablation; Survival